Impact of nitrogen-fixation bacteria on nitrogen-fixation efficiency of Bambara groundnut [Vigna subterranea (L) Verdc] genotypes - Bitire, Tope Daniel; Abberton, Michael; Tella, Esther Oluwabukunola; Edemodu, Alex; Oyatomi, Olaniyi; Babalola, Olubukola Oluranti (Frontiers in Microbiology, 2023)
Nitrogen fixation by bacteria is essential for sustaining the growth, development, and yield of legumes. Pot experiments were carried out at the International Institute of Tropical Agriculture (IITA) in the glasshouse between August to December 2018/2019 cropping season in Ibadan, Nigeria. Field studies were also performed in two different agroecological zones, “Ibadan and Ikenne” between August and December of 2019/2020 cropping season. The studies were set up to determine the potential of nitrogen-fixation bacteria strain inoculation on the nitrogen-fixation potential of 10 Bambara groundnut (BGN) genotypes, namely, TVSu-378, TVSu-506, TVSu-787, TVSu-1,606, TVSu-1,698, TVSu-1739, TVSu-710, TVSu-365, TVSu-475, and TVSu-305. The strains were inoculated as a broth to seedlings of each BGN genotype in the pot experiment. While six seeds from each BGN genotype were coated with each of the following nitrogen-fixation bacteria (Bradyrhizobium japonicum strains), FA3, USDA110, IRJ2180A, and RACA6, nitrogen fertilizer (urea, 20 kg/ha) was applied as a check to the nitrogen-fixation bacteria to seedlings of BGN genotypes 2 weeks after planting in both glasshouses and fields. Uninoculated plants served as controls (zero inoculation and zero fertilization). The field experiments were arranged in Randomized Complete Block Design (RCBD), while the glasshouse experiments were arranged in Complete Randomized Design (CRD) in triplicate. The result gotten showed that higher nodule numbers and weight were recorded in TVSu-1739 and TVSu-475 in both locations and seasons compared to other genotypes; the highest nitrogen fixed values were recorded among BGN genotypes TVSu-1739, TVSu-1,698, TVSu-787, TVSu-365, TVSu-305, TVSu-710, and TVSu-1,606, with a range of (62–67 kg ha−1), and were mostly enhanced by RACA6 and USDA110 strains compared to other strains that were used.